Parallel synthesis of potent dopaminergic N-phenyltriazole carboxamides applying a novel click chemistry based phenol linker - Loaiza, Pilar Rodriguez; Löber, Stefan; Hübner, Harald; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2009)
Taking advantage of our click chemistry based methodology to construct novel SPOS (solid phase organic synthesis) resins, the triazolylmethyl linked catechol 6a was discovered, which is readily available via copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) of azidomethyl substituted polystyrene with O-propargylcatechol and can be applied for the parallel synthesis of N-phenyltriazole carboxamides. As a proof-of-concept, a 'catch-and-release' strategy could be successfully applied for a parallel synthesis of dopaminergic phenyltriazoles of type 2. A focused model library of 20 test compounds revealing three points of diversity was generated by a three-step SPOS approach. Product purification was performed employing a solid-supported carboxylic acid anhydride as a scavenger. GPCR-ligand binding screening revealed dopamine D3 receptor ligands with K values in the single digit nanomolar range. © 2009 Elsevier Ltd. All rights reserved.